VISUAL OUTCOME AFTER INTRAVITREAL BEVACIZUMAB (AVASTIN) IN THE TREATMENT OF BRANCH RETINAL VEIN OCCLUSION - Naeem, Saquib; Rafe, Abdul (Pakistan Armed Forces Medical Journal, 2019)
Objective: To evaluate the visual outcome after intravitreal injection of bevacizumab (Avastin) in patients with branch retinal vein occlusion. Study Design: Prospective study. Place and Duration of Study: Combined Military Hospital (CMH) Kharian, from Mar 2016 to Nov 2017. Material and Methods: Patients of branch retinal vein occlusion (BRVO), were injected with minimum of one intravitreal bevacizumab 1.25 mg in 0.05 ml. Patients were examined using Snellen visual acuity testing, Fundus Fluorescein Angiography (FFA) and Optical Coherence Tomogragphy (OCT). Detailed eye examination was done before the procedure and follow-up visit on monthly basis was done for six months. Results: Twenty eight eyes of 28 patients were included, with a mean age of 63 years (SD 16.1). The patients received a mean of 3 (SD 1.30) injections of bevacizumab per eye. No adverse events were seen. At the baseline the mean central macular thickness was 559 microns which improved to 380 micron at 3rd month (p<0.001) and 300 microns after six months. The mean baseline acuity was log MAR = 0.70 (SD 0.19) and at three month log MAR=0.40 (SD 0.20); the difference was significant (p=0.001). At last follow-up of 6 months, the mean visual acuity was log MAR = 0.30 (SD 0.21), which was better than baseline (p<0.001). Twenty seven eyes showed improvement in visual acuity. Conclusion: Intravitreal bevacizumab caused substantial reduction in macular edema and enhancement in visual acuity. In this study the number of patients was limited and the follow-up was too short to makes recommendations of any specific treatment guidelines. Further studies are needed with long followup for treatment recommendations.